ANALISIS PENGARUH RASIO PROFITABILITAS, LEVERAGE, LIKUIDITAS, FIRM AGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP FINANCIAL DISTRESS - Tirza Chrissentia; Julianti Syarief (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
The condition of financial distress is a stage of corporate financial decline thatoccurred before a firm bankrupt. The purpose of this research is to analyze theinfluence of profitability, leverage, liquidity, firm age, institutional ownership of thepossibility of financial distress on non-financial services companies listed on theIndonesia Stock Exchange 2014-2016.The method of analysis used in this studyis binary logistic regression. Based on purposive sampling method, this studyobtained 89 companies as samples with 267 observation data. The results of thisstudy indicate that profitability, liquidity, firm age, and institutional ownership havea significant negative effect on the possibility of financial distress. Meanwhile, theleverage variable has a significant positive effect on the possibility of financialdistress.